EFEKTIVITAS JENIS ATRAKTAN YANG DIGUNAKAN DALAM OVITRAP SEBAGAI ALTERNATIF PENGENDALIAN VEKTOR DBD DI KELURAHAN BULUSAN - Asriati Wahidah; Martini Martini; Retno Hestiningsih (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Ovitrap use is a method of Aedes sp. control which quite effective without using insecticides and it successfully reduces vector density in some countries. This research aims to determine effectiveness of various types of attractant used in ovitrap that are using hay infusion, yeast tape water, tiger shrimp immersion waterand ordinary water as the control for alternative DHF vector control in Bulusan Village. This research used quasi experimental approach with post test only control group design study. The samples were selected by using purposive sampling and consist of 15 houses in Bulusan Village. The result of Kruskal-Wallis analysis with p=0.058 showed no significant difference between the number of Aedes sp. eggs that trapped by various types of attractant. The total number of eggs were trapped on ovitrap are 436 eggs. The average number of eggs that most trapped is in ordinary water (control), consist of 2,73 eggs/ovitrap outside the house and 13,13 eggs/ovitrap inside the house; 5,06 eggs/ovitrap trapped in hay infusion outside the house and 3,33 eggs/ovitrap inside the house; 4 eggs/ovitrap trapped in yeast tape water outside the house and 0.6 eggs/ovitrap inside the house. The less number of eggs were in tiger shrimp immersion water that consist of 0,13 eggs/ovitrap outside the house and no egg/ovitrap inside the house. The percentage of Ae.aegypti is 78.22%, higher than Ae. albopictus that only 21.78%. Public Health authorities are expected to disseminate the use of ovitrap as one of alternatives control of DHF vector.